Evaluasi Pelaksanaan Standar Sekolah Sehat dan Aman di SDN 6 Kendari: Evaluasi Pelaksanaan Standar Sekolah Sehat dan Aman - Qadri, Muhammad Saleh; Yasin, as; Wati, Risnah; Milida, Rizkia; Nur Ainun, Rizkita (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The implementation of healthy and safe school standards is a strategic effort to create a learning environment that supports the health and safety of elementary school students. This study aims to evaluate the implementation of healthy and safe school standards at SDN 6 Kendari, which is characterized by its proximity to a market and a main road. The study employed a qualitative approach using a case study design, involving field observations, the completion of a healthy and safe school indicator questionnaire, and interviews with educators. The results indicate that SDN 6 Kendari has met most of the healthy school indicators, evidenced by well-maintained buildings, adequate ventilation and lighting, proper sanitation and waste management, and students’ consistent practice of clean and healthy living behaviors. Regarding the safe school aspect, the school’s social environment is relatively conducive and free from risky behaviors, supported by the availability of a monitoring system and collaboration with relevant parties. However, several areas still require improvement, such as the equitable distribution of handwashing facilities, more strategic placement of portable fire extinguishers, and strengthening traffic risk mitigation measures due to the school’s location. Overall, the implementation of healthy and safe school standards at SDN 6 Kendari has been proceeding well, but requires continuous improvement to achieve optimal compliance with the standards.